QUALITY OF LIFE AND ENVIRONMENT SUSTAINABILTY-YES OR NO? - Ristić, Nikola; Gavrić, Olga (Economics of Agriculture, 2024)
Quality of life and preserved eco-systems are important characteristics of sustainability and well-being. The aim of the paper is to analyze the relationship between the Legatum Prosperity Index, as the measure of quality of life and Environmental Performance Index, as a measure of the multidimensional ecological achievement. The research has covered 27 EU countries and applied statistical methods: simple linear correlation and cluster analysis. In this regard, the analysis showed the existence of a statistically significant relationship between these two composite indices. In other words, economically developed countries in which the quality of life is at a high level have better environmental performance, and vice versa.